Some marine algae from Mauritius - Boergesen, F. (Ejnar Munksgaard, 1940)
Contents: I. Chlorophyceae II.PhaeophyceaeIII. Rhodophceae part 1.Porphyridiales, Bangiales, Nemalionalespart 3.Rhodymeniales part 4. Ceramiales-Additional lists to the Chlorophyceae and Phaeophyceae